Thermomagnetic convection in stratified ferrofluids permeated with dusty particles through a porous medium (Journal of Basic and Applied Research in Biomedicine, 2022)
In the present note, the stability problem of an incompressible dusty stratified ferromagnetic fluid is investigated through a porous medium when the fluid layer is subjected to vertical magnetic field intensity. The governing nonlinear equations are linearized using perturbation technique and the cases of exponentially varying stratifications for various physical parameters are discussed. The system is found to be stable for stable stratification in both the absence and presence of magnetic field. For unstable stratification, the system has both stabilizing and destabilizing effects in the presence of magnetic field under certain conditions, whereas in the absence of magnetic field, the system has only destabilizing effect. The variations in the growth rate with respect to kinematic viscosity, medium porosity, medium permeability, square of Alfvén velocity and suspended particle parameter are also shown analytically.